Two-Dimensional DoA Estimation for Multipath Propagation Characterization Using the Array Response of PN-Sequences - Zhang, Ruonan; Wang, Shichao; Lu, Xiaofeng; Duan, Weiming; Cai, Lin (IEEE transactions on wireless communications, 2016)
Multipath propagation and power arrival profiles in three-dimensional (3-D) space determine the performance of the full-dimensional MIMO (FD-MIMO) systems. Field channel measurements are crucial in characterizing wireless channel properties. Nevertheless, in spatial channel measurements, estimating the direction-of-arrivals (DoAs) of multipath components (MPCs) is a challenging issue, because of the large number of propagation paths and the correlation among the multipath signals. The number of incidence angles and estimation precision in traditional methods is limited by the sensor array size and signal correlation. In this paper, we propose a scheme for measuring and estimating the 2-D DoAs of propagation paths called multipath angular estimation using the array response of PN-sequences (MAPS). By using a receiving planar antenna array (PAA), MAPS first extracts the complex path array response vector (PARV) for each propagation path and then estimates the DoAs of the paths individually and independently. The subspace-decomposition theory for MAPS is proved and extensive simulations are conducted to compare MAPS with other algorithms. Furthermore, a channel sounder using two PAAs and the probing signal of 2.6 GHz carrier modulated by PN-sequences has been developed. The simulation and field tests show that MAPS can estimate arbitrary number of resolved MPCs in a channel snapshot and effectively suppress the multipath interference.